Stages and main tasks of the century-long control theory and system identification development. Part II. Methods for designing linear controlsystems based on mathematical models of input-output processes - Romanenko, V.; Gubarev, V. (Проблеми керування та інформатики, 2023)
The article provides an overview of the mathematical description of the dynamics of continuous and discrete linear stationary systems and objects, applied during the development of classical automatic control theory in the form of input-output type mathematical models. The time and frequency characteristics of continuous and discrete control systems are described, typical components of stationary systems are discussed, and parametric discrete models of objects in typical digital control loops are presented. Stochastic discrete autoregressive models of stationary time series are considered, which are used to describe the dynamics of objects in the synthesis of digital control systems. An overview of typical control laws for implementing continuous and discrete regulators is given. У статті виконано огляд математичного опису динаміки неперервних та дискретних лінійних стаціонарних систем та обʼєктів, що застосовується на етапі розвитку класичної теорії автоматичного керування у формі математичних моделей типу «вхід–вихід». Описано часові та частотні характеристики неперервних та дискретних систем керування, розглянуто типові ланки стаціонарних систем, наведено параметричні дискретні моделі обʼєктів у складі типових контурів цифрового керування. Розглянуто стохастичні дискретні авторегресійні моделі стаціонарних часових рядів, які застосовуються для опису динаміки обʼєктів при синтезі цифрових систем керування. Здійснено огляд типових законів керування для реалізації неперервних та дискретних регуляторів.